Mozgóképek Bartókról - Sülyi, Péter, 1950- (Hungary : MTV, 1988)
The widow of TIbor Serly living in the USA in 1988 sent an unknown, short amateur movie without sound about Béla Bartók composer. In the movie the composer is playing a piano. The director is able to create sound for the movie.
Keywords: Documentary films